Prolactin and autoimmune diseases in humans - Chuang, Ellie; Molitch, Mark E. (Acta Biomedica Atenei Parmensis, 2007)
Prolactin has been shown to have immunomodulatory as well as lactogenic effects. Generally less well known is that prolactin may also play a role in the activity of autoimmune diseases such as systemic lupus erythematosus and rheumatoid arthritis. Studies have shown decreasing prolactin production to be beneficial in animal models of autoimmune disease. Thus far, double-blinded, placebo-controlled studies of dopamine agonist treatment in humans with autoimmune disease have been done only in lupus patients, and support the potential efficacy of such agents. Small, open-label trials have also suggested potential benefit in patients with rheumatoid arthritis, Reiter’s syndrome, and psoriasis. More studies are required to further delineate the mechanisms by which prolactin affects autoimmune disease activity, to determine in which specific diseases prolactin plays a significant role, and to test the efficacy of prolactin-lowering agents as therapy for such diseases.